Initial material for breeding drought-resistant varieties of spring barley in the conditions of the Volga-Vyatka region - Zaytseva I. Yu.; Mamaeva L.V.; Shchennikova I. N.; Kokina L. P.; Dyagileva E. V. (E3S Web of Conferences, 2021)
Water scarcity has a significant impact on plants, quality and quantity of crops. On the soils of the northeast of European Russia, instability of precipitation is one of the main factors negatively affecting barley productivity. To assess the drought tolerance level, we used the RSR (root-to-shoot ratio) indicator, which shows the relative redistribution of fluxes of plastic substances between root and aerial organs. Evaluation of 57 collection accessions of spring barley of various ecological and geographical origins was carried out. As a result of the research, sources of breeding of valuable traits were identified for further breeding work on the creation of barley varieties adaptive to the conditions of the Volga-Vyatka region. The accessions Bonita, Bionic, Cooper, Danuta, 752A, NCL 95098, local sample from India (k-3506), Odessky 115, Rodos, Kazminsky, Polarny 14, Adam, Bear, Medicum 11, Irbe (PR-3528), Mie, 121–13, and C-105 are characterized by resistance to osmotic stress at the early stages of organogenesis. For further breeding work drought-resistant varieties NCL 95098, Cooper, Bonita, Danuta, Mie, Rodos, Kazminsky, Adam, Bear, Medicum 11, Irbe (PR-3528), 752A, Polarny 14, and C-105, distinguished by the elements of plant productivity, are advisable to use taking into account their positive qualities. The rest of the drought-resistant accessions are recommended to be included in crosses with varieties having higher productivity.